A materiality approach to moveable containers in the Indus tradition. (March 2023) - Bates, J.
Abstract: The "humility of things", their physicality and often mundanity, can allow objects to escape our notice in the everyday whilst also making them indispensable to our daily lives. Affordances, the potential relationships that form when people and objects interact, relationships shaped by the physical properties of the objects, further enmesh material culture and people. This paper applies these concepts to a particular group of objects from the Indus Civilization of South Asia (c.3200-1500 BCE), moveable containers. This paper uses a sensorial materiality and affordances approach to the concept of containment and containers to look at how the affordances of containers may have shaped the interactions people had with them, and how containers may have influenced the choices people made about materials. This paper argues that a more phenomenological materialism could provide a new light on the discussion of the interactions between Indus people and their material world. Highlights: Objects are entangled, active agents, engaged in relationships with us and the world. Material affordances enmeshes material culture and people. Indus Tradition containers are often analyzed by the material they are made from. Looking at containers as a group and their affordances our perspectives change. Phenomenological materialism gives new insight Indus people and their material world.